Credence Goods Markets with Fair and Opportunistic Experts - Heinzel, Joachim Maria Josef
We analyze a credence goods market adapted to a health care market with regulated prices, where physicians are heterogeneous regarding their fairness concerns. The opportunistic physicians only consider monetary incentives while the fair physicians, in addition to a monetary payoff, gain an non-monetary utility from being honest towards patients. We investigate how this heterogeneity affects the physicians’ equilibrium level of overcharging and the patients’ search for second opinions (which determines overall welfare). The impact of the heterogeneity on the fraud level is ambiguous and depends on several factors such as the size of the fairness utility, the share of fair physicians, the search level and the initial fraud level. Introducing heterogeneity does not affect the fraud or the search level when the share of fair physicians is small. However, when social welfare is not at its maximum, social welfare always increases if we introduce a sufficiently large share of fair physicians.
Keywords: credence goods; heterogeneous experts; fairness; overcharging